THE INFLUENCE OF LAND AREA, PALM OIL PRODUCTION AND LABOR ON GROSS REGIONAL DOMESTIC PRODUCT IN ACEH PROVINCE - Ichwan Musara Yoga; Cut Putri Mellita Sari; Noviami Trisniarti (Universitas Efarina, 2022)
The purpose of this study is to investigate how palm oil production, labor, and land area affect Aceh province. This study relies on secondary data for the years 2016 to 2020 that can be accessed at www.bps.go.id. Using Eviews 9 Software, panel data regression analysis was used to analyze the data. According to the findings of this study, production has a significant impact on Gross Regional Domestic Product bruto (PDRB) while land area has no effect on PDRB in Aceh Province. In Aceh Province, labor has no significant negative impact on PDRB. In the meantime, in Aceh Province, land area, production, and labor all have a positive and significant impact on PDRB simultaneously. This study suggests that district and city governments in Aceh Province should pay more attention to the area of oil palm land and oil palm small holders for the community in order to increase district and city PDRB.